Sources of Industrial Growth Using Factor Decomposition Approach: Malaysian Experiences, 1978-87 - Elameer, Ahmed Elyas (1997)
The main objective of the study is to examine sources of industrial output growth of the Malaysian economy, which has undergone changes in its trade policy from import substitution to export orientation strategies. To fulfill this objective, sources of industrial growth are analysed by factor decomposition approach (i.e. demand side analysis) This approach decomposed output growth of each industry into its four sources namely, export expansion, import substitution, intermediate demand expansion and domestic demand expansion. Input-output tables for the years 1978, 1983 and 1987 which were published by the Department of Statistics were used in this study. The overall period between 1978 to 1987 has been divided into two sub-periods, that is 1978-1983 and 1983-987. The 1983 and 1987 tables were deflated to their 1978 constant prices using both sectoral producer price and sectoral import price indices. The results of the study indicate that the domestic demand expansion has been the dominant source of growth of the overall Malaysian economy in 1978-83. The study also shows that the industrial growth was due to the export expansion during 1983-87 and the overall period. The manufacturing sector appears to play a crucial role in the country's growth process. Its contribution to the overall economic growth has steadily increased. Most important among the manufacturing sub-sectors is the electrical machinery industry. This study concludes that while it is important to continue pursuing export oriented strategy to achieve growth objectives, it has to balance it out with an appropriate policy to reduce import of intermediate and capital goods.